A Double Punishment: The Context of Postsecondary Access for Racialized Precarious Status Migrant Students in Toronto, Canada - Villegas, Paloma E.; Aberman, Tanya (Refuge, 2019)
This article examines how the immigration and schooling systems in Canada intersect to deny access to migrant youth with precarious status throughout educational trajectories. While there are access policies at the primary and secondary school level, barriers increase in post-secondary education. We argue that such students transitioning to university experience a “double punishment” through racialized exclusion in the education and immigration systems. Our research draws from semi-structured interviews with migrant youth and our experience organizing an access program at York University that targets precarious status students for inclusion. We propose that Canadian universities and policymakers learn from such access programs to increase equitable inclusion at other institutions.